Life history strategies of a trimorphic population of Arctic charr (Salvelinus alpinus (L.)) in Skogsfjordvatn, northern-Norway - Smalås, Aslak (Universitetet i Tromsø, 2013)
Polymorphisms are widespread throughout many different taxa of vertebrates. Discrete polymorphisms or morphs usually differentiate in morphology, ecology and life history, most likely driven by adaptations to different habitats and resources. For sympatric morphs to be able to maximize fitness in different niches and habitats, they may develop differences in several life history traits. Arctic charr (Salvelinus alpinus (L.)) is a good model species for verifying and understanding ecological driven polymorphism and speciation. Here, I address the life history traits of three sympatric living Arctic charr morphs in Skogsfjordvatn in northern Norway. The charr morphs differ in diet and habitat utilization; including one morph that feeds on benthic invertebrates and zooplankton in the littoral-pelagic zone (referred to as the LO-morph), a second that feeds on chironomids and small mussels in the profundal zone (PB-morph), and a third that also inhabits the profundal zone, but has a piscivorous diet (PP-morph). The littoral and the two profundal spawning morphs are differentiated in time and place of spawning and all morphs are genetically differentiated, indicating complete reproductive isolation. These morphs also had contrasting differences in numerous life history traits.